2010
DOI: 10.1111/j.1758-5740.2010.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Long Philos Plate Fixation for Complex Humeral Fractures

Abstract: Background Operative stabilisation of long segment periarticular, periprosthetic and pathological fractures in humerus is a challenging problem. Methods A total of 18 patients were treated by open reduction and internal fixation using the long proximal humeral internal locking system (PHILOS) plate. The types of fractures treated were long segment periarticular fractures extending into the diaphysis (11 of 18), periprosthetic fractures around humeral resurfacing (five of 18) and pathological fractures (two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Both nailing and plating techniques have been described so far for the treatment of displaced proximal metadiaphyseal humerus fractures with reasonable results [1][2][3]6,17]. Although minimally invasive approaches can be applied using indirect methods for fracture reduction, a single extensile approach is usually necessary [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both nailing and plating techniques have been described so far for the treatment of displaced proximal metadiaphyseal humerus fractures with reasonable results [1][2][3]6,17]. Although minimally invasive approaches can be applied using indirect methods for fracture reduction, a single extensile approach is usually necessary [1].…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, additional iliac crest autograft with or without augmentation with strut grafts should be applied to facilitate fracture healing [18]. Apart from metadiaphyseal fractures, humeral shaft fractures and nonunions with poor bone stock that require long plate fixation and multiple screws insertion to proximal metaphysis and humeral head for achieving construct stability are also candidates for application of the method [17].…”
Section: Discussionmentioning
confidence: 99%
“…13 A study of 18 long PHILOS plate fixations for a mixture of pathologies by Pimple et al reported no non-unions, with a mean residual pain of 0.8 as assessed by the VAS. 5 The results of this series, which looked purely at nonpathological fractures and excluded peri-prosthetic fractures, compare unfavourably with a non-union rate of 12% and a mean residual pain of 3.6 on the VAS scale. On analysis of the nonunions, we could not identify any specific predisposing factors to predict non-union but are limited in analysis by the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The one English language paper on the subject is a mixed series involving traumatic, pathological and peri-prosthetic fractures. 5 The present study aimed to assess the medium-term results of traumatic proximal humerus fractures with distal metaphyseal or diaphyseal extension treated with long contoured proximal humerus internal locking system (PHILOS) plates (Synthes, Stratec Medical, Oberdorf, Switzerland).…”
Section: Introductionmentioning
confidence: 99%
“…However, fixation of proximal and distal fractures is not possible with the anterior opening MIPO technique. For this purpose, it has been reported in a limited number of studies that extended segment fractures could be treated by using the anatomical PHILOS plate (2,8,9). Hence, it is possible to protect the deltoid insertion, to use the distal anterior surface for fixation of the distal screws, and to move away from the radial nerve zone by applying PHILOS plates that are helically shaped manually.…”
Section: Introductionmentioning
confidence: 99%